Detection of Lophomonas blattarum (Order: Hypermastigida) from Iranian Patients with Allergic Rhinitis - Mehdi Bakhshaee; Yeganeh Teimouri; Farahzad Jabbari Azad; Razieh Yousefi; Mahmoud Parian; Fariba Berenji (Iranian Journal of Parasitology, 2022)
Background: Allergic rhinitis (AR) is one of the most common allergic diseases triggered by indoor and outdoor allergens. Certain arthropods, such as mites and cockroaches, contain protozoa like Lophomonas blattarum in their intestines to help with digestion that may have some role in AR. We aimed to determine the frequency of L. blattarum in nasal smears of patients with AR in comparison with healthy controls.